Time and replacement among the Q’eqchi’ Maya - Paul Kockelman (Journal de la Société des Américanistes)
Among speakers of Q’eqchi’ Maya, replacement (–eeqaj) refers to activities as disparate as house-building, civil-religious elections, vengeance, loans, illness cures, adultery, and namesakes. Such practices involve the substitution of one entity for another entity, insofar as these entities have shared properties, and insofar as they hold a role in an obligatory position. For example, one man may substitute his labor for another man’s labor insofar as men have similar degrees of strength and skill, and insofar as a position in a labor-pool must be filled. In this paper, I explore the relation between replacement, as an idea and institution, and ‘lived time’. To do this, I offer five different ways of framing temporality (as repetition, irreversibility, roots and fruits, reckoning, and worldview); and I show how replacement may be figured through each of these frames. Along the way, I show how entities caught up in replacement are different from other items of value, such as singularities and commodities; and I offer an entity-centered, as opposed to event-centered, framing of time.